Effect of shoulder\'s centralized exercise and pushrim activated power assisted wheelchair on shoulder pain and function veterans affected by paraplegic spinal cord injury - F. Babakhani; R. Balouchi; M.R. Vahidian (Afarand Scholarly Publishing Institute, 2018)
Aims: Spinal cord injury is an acute and devastating event that causes significant and permanent changes in veterans' life and leads to functional impairments. Exercise can reduce the incapacity or improve individuals' functions. The aim of this study was to investigate the effect of shoulder centralized exercises and Pushrim-Activated Power-Assisted Wheelchair (PAPAW) on pain and shoulder function in veterans with paraplegic spinal cord injury. Materials & Methods: In this semi-experimental study with pre-test and post-test design, 20 wheelchair-user veterans with spinal cord injury and shoulder pain referring to Kosar orthosis and prosthesis center were selected by purposive sampling in 2015. They were randomly assigned into experimental (n=10) and control (n=10) groups. Data were collected by Wheelchair Userchr('39')s Shoulder Pain Index (WUSPI) and Shoulder Rating Questionaire (SRQ). The exercises were performed for 8 weeks and 3 days each week in the experimental group with using Pushrim-Activated Power-Assisted Wheelchair (PAPAW) at home and the control group did not receive any interventions. Data were analyzed by dependent t-test and Analysis of Covariance (ANCOVA). Findings: In the experimental group, the pain level significantly decreased and the shoulder function significantly increased in the post-test compared to the pre-test. There was a significant difference between experimental and control groups (p<0.05). Conclusion: Shoulder centralized exercises and Pushrim-Activated Power-Assisted Wheelchair (PAPAW) is effective on decreasing the pain and increasing shoulder function in veterans with paraplegic spinal cord injury.